Impact of compact diffuser shroud on wind turbine aerodynamic performance: CFD and experimental investigations. (15th February 2022) - Alkhabbaz, Ali; Yang, Ho-Seong; Tongphong, Watchara; Lee, Young-Ho
Highlights: An optimization approach is performed to obtain an efficient and compact shroud profile. The aerodynamic performance of both the bare rotor and the equipped rotor with an optimized shroud is analyzed using CFD approach. A systematic comparison of CFD results with the corresponding experimental data is implemented. The power coefficient ( Cp ) obtained from the Shrouded rotor increased by approximately 66.4% compared to the bare rotor. Abstract: In the present work, the influence of a compact diffuser on aerodynamic behavior of small-scale wind turbine is analyzed using both CFD and experimental approaches. The present work aims to obtain a compact diffuser shroud while ensuring high aerodynamic performance in order to reduce the fabricating costs, materials, and structural loads on the mast. In this regard, a unique optimization approach is employed to optimize the geometrical features of the shroud profile including length of both entrance and diffuser sections, radii of both diffuser and entrance area. The shroud profile is mathematically described using second-order polynomial functions. The optimization findings affirmed that the total length of optimized shroud profile is shorter by approximately 6 % than the baseline ( Cii ) configuration. However, the wind speed obtained from the optimized shroud profile shows an improvement of 1.58% compared to the baseline configuration at the throat area. A high-fidelity CFD simulation of the wind turbine equipped with an optimized shroud profile using commercial software SATR-CCM+ was performed to evaluate the overall aerodynamic performance of the wind lens system. Both conventional and shrouded wind turbines were investigated for two different cases: constant rotor speed, and constant wind speed. Furthermore, an experimental test was implemented for both conventional and shrouded turbines under various environmental conditions using an open-loop wind tunnel. A systematic comparison between CFD results with the corresponding experimental data for both turbines is performed. It is evident that placing an optimized shroud around the rotor improves the aerodynamic performance more than twofold compared to the bare turbine. Moreover, results revealed that Cp obtained from shrouded Wind Turbine increased by approximately 66.4 % compared to the conventional one based on CFD results, whereas, it has increased by 69.3 % according to the experimental data. Graphical abstract: Image, graphical abstract